Immigration and Crime: New Empirical Evidence from European Victimization Data - Luca Nunziata (Institute for the Study of Labor (IZA), 2014)
We exploit the increase in immigration flows into western European countries that took place in the 2000s to assess whether immigration affects crime victimization and the perception of criminality among European natives. Using data from the European Social Survey, the Labour Force Survey and other sources, we provide a set of fixed effects and instrumental variable estimations that deal with the endogenous sorting of immigration by region and with the sampling error in survey based measures of regional immigration shares, whose implications in terms of attenuation bias are investigated by means of Monte Carlo simulations. Our empirical findings show that an increase in immigration does not affect crime victimization, but it is associated with an increase in the fear of crime, the latter being consistently and positively correlated with the natives' unfavourable attitude toward immigrants. Our results reveal a misconception of the link between immigration and crime among European natives.
Keywords: J15; J61; K42; F22; R23; O15; 330; crime; migration; victimization; perception; fear